Epithelial Ovarian Cancer: Real-World Outcomes - Nakka, Thejeswar; Ganesan, Prasanth; Goenka, Luxitaa; Dubashi, Biswajit; Kayal, Smita; Chaturvedula, Latha; Papa, Dasari; Penumadu, Prasanth; Krishnamoorthy, Narendran; Thumaty, Divya B. (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Ovarian cancer is the third most common cancer and the second most common cause of death among gynecological cancers in Indian women. Ovarian cancer is heterogeneous, among them, epithelial ovarian cancer (EOC) is the most common. Primary cytoreductive surgery along with six to eight cycles of a combination of platinum and taxanes chemotherapy is the cornerstone of first-line treatment in EOC. This study was done to find clinicopathological factors affecting survival outcomes with first-line therapy in EOC in a real-world setting.Objectives This study was aimed to find factors affecting progression-free survival (PFS) and overall survival (OS) with first-line treatment in EOC.Materials and Methods We conducted a single-center retrospective study. We screened all the patients diagnosed with ovarian cancer from January 2015 till December 2019. We locked data in August 2019. Eligible patients were histologically confirmed EOC who underwent primary cytoreduction or received more than or equal to two cycles of chemotherapy or both. Patients who had received first-line treatment at another hospital were excluded.Results Patients demographics and clinical characteristics: between January 5, 2015 to August 31, 2019, 435 patients with a diagnosis of ovarian malignancy were registered at our center. Among them, 406 (82%) had EOC, 290 (64%) newly diagnosed, and fulfilling eligibility criteria were included in the final analysis. The median age of the cohort was 53 years (range: 21–89 years) and 157 patients (54%) were >50 years of age (the Eastern Oncology Cooperative Group Performance status was ≥ 2 in 124 patients [43%]; median duration of symptoms was 3 months; and stage III/IV: 240 [83%]). Grading of the tumor was available in 240 patients of which 219 (91%) were of high grade. Subtyping was available in 272 patients (94%) of which the serous subtype was the most common constituting 228 patients (79%).Treatment Most patients received chemotherapy (n = 283 [98%]) as the first modality of treatment (neoadjuvant/adjuvant and palliative). As neoadjuvant (NACT) in 130 patients (45%) and as adjuvant following surgery in 81 patients (29%). The most common chemotherapy regimen was a combination of carboplatin and paclitaxel in 256 patients (88%). Among 290 patients 218 (75%) underwent cytoreductive surgery. Among them, optimal cytoreduction was achieved in 108 patients (52%). Optimal cytoreduction rate (OCR) with upfront surgery and after NACT was 44 and 53%, respectively (Chi-square test: 0.86; p = 0.35).Survival The median follow-up of the study was 17 months (range: 10–28 months) and it was 20 months (range: 12–35 months) for patients who were alive. At last, follow-up, 149 patients (51%) had progressed and 109 (38%) died. The estimated median PFS and OS were 19 months (95% CI: 16.1–21.0) and 39 months (95% CI: 29.0–48.8), respectively. On multivariate analysis, primary surgery (HR: 0.1, 95% CI: 0.06–0.21; p-value: <0.001) and early-stage disease (HR: 0.2, 95% CI: 0.1–0.6; p-value 0.04) were associated with superior PFS and primary surgery (HR: 0.1, 95% CI: 0.09–0.2; p-value: <0.001) was associated with superior OS.Conclusion Primary surgery (upfront or interval) was associated with improved survival. Newer agents like bevacizumab, poly-ADP (adenosine diphosphate)-ribose polymerase inhibitors and HIPEC should be incorporated precisely into first line of therapy to improve outcomes.
Keywords: epithelial ovarian cancer; progression-free survival; overall survival